
 👍 0
 👎 0
posted by Steve 
 👍 0
 👎 0
posted by tom 
 👍 0
 👎 0
posted by Steve 
 👍 0
 👎 0
posted by tom 
 👍 0
 👎 0
posted by tom 
 👍 0
 👎 0
posted by Steve
Respond to this Question
Similar Questions

math
Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8
asked by Anonymous on October 25, 2018 
math,correction
Can somoene helpme plz... Simplify radical 7 * radical 14 wouldn't it be radical (7*14) = radical (98) = 7radical (14) = 7 radical (2) The result is right, you erred on the next to last line. So how do i show that step that i am
asked by jasmine20 on March 29, 2007 
Math
The area of one of the faces of the cube below is x^2+2x+1 cm^2. Find an expression in mixed radical form for the length of the interior design. My Work: Step 1: a^2 + b^2 = c^2 =(x1)(x1) x1 equals to all the sides of the cube
asked by Angel on November 16, 2016 
Algebra help
f(x)=x^34x^2x+4 How do I find the xintercept for this? This is from my book: step 1: 0=x^34x^2x+4 step 2: 0=x^2(x4)+(1)(x4) step 3: 0=(x^21)(x4) I know how to solve once I get to step 3, but in step 2, I don't know what
asked by Claure on June 16, 2009 
Math PreCalc.
Determine the domain and range of y= (radical) x4 y= (radical) x^24 plz help me step by step. I just need to refreash my math, but i forgot how to find it
asked by Soraya on August 23, 2009 
math
An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,
asked by oscar on September 4, 2015 
math
An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,
asked by oscar on September 4, 2015 
mathradical equations
Here's one of the questions I have problems with: cube root of (x+2)=6th root of (9x+10) A. 1, 6 B. [13 +/ sqrt(193)]/2 C. 1, 6 D. [13 +/ sqrt(145)]/2 Please explain how to solve this. Should you cube both sides, or raise
asked by Jennifer on May 4, 2008 
mathradical equations
Here's one of the questions I have problems with: cube root of (x+2)=6th root of (9x+10) A. 1, 6 B. [13 +/ sqrt(193)]/2 C. 1, 6 D. [13 +/ sqrt(145)]/2 Please explain how to solve this. Should you cube both sides, or raise
asked by Jennifer on May 4, 2008 
Physics
Can someone please show me step by step how to normalize e^5x in the interval (0, infinity)? I have read a lot of different books etc but need it explained to me in plain English or showed to me step by step because I am just not
asked by Tammy on September 16, 2011